Institutional Challenges in the Laws of Iran\'s 2025 Vision Document and Subordinate Plans - Moosa Ghafouri; Ebrahim Barzegar (Iranian Journal of Educational Research)
Objective: A vision document represents an idealized depiction of the future, highlighting the long-term objectives of a nation. When discussing the analysis of perspectives on both the national and global scale, it is crucial to reassess the internal and external indicators of the education system. The objective of this article was to investigate the institutional challenges presented in the laws of the Iran vision document 2025 and its subordinate plans. Methods: The research methodology employed was primarily applied, with a descriptive-analytical and survey approach. The population for this study consisted of the development perspective document of the Islamic Republic of Iran for the horizon of 2025, as well as the fourth, fifth, and sixth development plans of the country, and the performance of the annual budget during the implementation of the development perspective document of 2025. Data collection involved the utilization of both document analysis and survey methods. The process tracking method was employed to analyze the data, search for evidence, and evaluate it in order to elucidate the reasons behind the unaccomplished goals of the 2025 vision document. Results: Consequently, an effective and dependable system for measurement and evaluation becomes imperative to assess and monitor progress in the realization of long-term visions and plans. However, there are instances where the measurement and evaluation system prove to be inefficient and incomplete, which hinders the identification and rectification of weaknesses, as well as performance enhancement. The implementation of the vision document and its subsequent programs may necessitate substantial financial resources. Inadequate funding or insufficient budget allocation can lead to financial difficulties and delays in the execution of these programs. Conclusions: To advance with the vision document and downstream plans, it is essential to identify and manage these barriers.